PENGARUH DANA BANTUAN SEKOLAH (BOS) TERHADAP KINERJA PENDIDIKAN SEKOLAH SMK SWASTA SE-KOTA MEDAN (TAHUN 2018) - Ayu Ade Riyanti; Listya Devi Junaidi (Worksheet : Jurnal Akuntansi, 2022)
The purpose of this study is to ascertain whether school aid funds (BOS) have an impact on academic achievement. In this work, quantitative descriptive techniques are also used. Secondary data, or data that does not directly supply data to data collectors, was employed in this study. To conduct this study, a purposive sample technique was applied throughout as many as 55 private vocational high schools in Medan. purporsive sampling method, or the method of choosing the sample while taking particular factors into account. This study uses a straightforward linear regression analysis strategy for data analysis. In this study, there are 2 (two) variables: an independent variable (the independent variable) and a dependent variable (the dependent variable), both of which are impacted by and subject to the effects of causes that result from change. The data will next be analysed using the Classical Assumption Test and hypothesis testing with the aid of SPSS 24.The test results from this study show that there is, at least in part, a relationship between School Operational Assistance Funds and Educational Performance / Achievement of National Examination scores using the t test, whereas there is no relationship between Accreditation Status (a), (b), and (c) and the level of educational performance / achievement of national exam scores. This is due to the fact that formal education institutions, particularly vocational high schools, are present in every part of Medan City.